Everyone in my family has killed someone [large type] - Stevenson, Benjamin (Harper Large Print, an imprint of HarperCollins Publishers, 2023)
"Everyone in my family has killed someone. Some of us, the high achievers, have killed more than once. I'm not trying to be dramatic, but it is the truth. Some of us are good, others are bad, and some just unfortunate. I'm Ernest Cunningham. Call me Ern or Ernie. I wish I'd killed whoever decided our family reunion should be at a ski resort, but it's a little more complicated than that. Have I killed someone? Yes. I have. Who was it? Let's get started"--